Word and power in mediaeval Bulgaria - Biliarski, Ivan 1959- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2011)
The law is a cultural phenomenon that impacts on the whole normative system of a civilisation and finally its core values. It is part of and simultaneously protector of these values. As such the law is in close relation with identity and with one of its main transmitters - the language. Every civilisation has a law code that should be common to all its parts and members and should be based on a common lexis. This book presents a case study in the legal terminology of mediaeval Bulgaria displayed against the broader background of the Byzantine civilisation to which the country belonged. It is accompanied by a glossary of the juridical lexis that is not only an example but forms the very basis of the researc project.